Home Pulse Rate Before and During Antihypertensive Treatment and Mortality Risk in Hypertensive Patients: A Post Hoc Analysis of the HOMED‐BP Study - Takahiro Kimura; Masahiro Kikuya; Kei Asayama; Yukako Tatsumi; Yutaka Imai; Takayoshi Ohkubo (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Although a high pulse rate assessed in the clinic office setting has been associated with an increased risk of cardiovascular disease and mortality, there are few studies assessing the prognostic ability of out‐of‐office pulse rate, particularly self‐measured home pulse rate. Methods and Results We investigated the prognostic ability of home pulse rate in 3022 patients with mild‐to‐moderate hypertension. During a median follow‐up of 7.3 years, 72 patients died and 50 had major adverse cardiovascular events. For each 1 SD increase in pulse rate before treatment (9.4 beats per minute), the adjusted hazard ratio for all‐cause mortality was 1.52 (95% CI, 1.24–1.92). For each 1 SD increase in pulse rate during the follow‐up period (9.9 beats per minute), the adjusted hazard ratio was 1.70 (95% CI, 1.39–2.08). However, pulse rate was not significantly associated with major adverse cardiovascular events. When both home pulse rate and office pulse rate before treatment were included in a Cox model, only the home pulse rate significantly predicted all‐cause mortality (P ≤0.019). Excluding the home pulse rate from the model led to a significant deterioration of the model fit statistic (P ≤0.020). The optimal cut‐off values of home pulse rate in predicting all‐cause mortality, determined by Youden's index from a receiver operator characteristic analysis, were 67.8 beats per minute at baseline and 66.4 beats per minute during follow‐up. Conclusions In patients with mild‐to‐moderate hypertension, the pulse rate measured at home, both before and during antihypertensive treatment, was associated with mortality risk and has superior prognostic ability compared with office pulse rate. The accuracy of risk stratification may be improved by using a home pulse rate, which can be self‐measured easily and frequently at home. Registration URL: https://www.umin.ac.jp/ctr; Unique identifier: C000000137.